Associations between variation in the ovine high glycine-tyrosine keratin-associated protein gene KRTAP20-1 and wool traits. (8th December 2018) - Gong, Hua; Zhou, Huitong; Bai, Lingrong; Li, Wenhao; Li, Shaobin; Wang, Jiqing; Luo, Yuzhu; Hickford, Jon G H
Abstract: The keratin-associated proteins (KAP s) are important constituents of wool fibers. Of the many mammalian KAP genes ( KRTAPs ) identified, KRTAP20-1 has been described in humans, but it has not been described in any other species. A search of the sheep genome using the human KRTAP20-1 sequence revealed a homologous open reading frame on chromosome 1, which would encode a high glycine-tyrosine KAP. PCR-single-stranded conformational polymorphism (PCR-SSCP ) analysis identified 8 different banding patterns representing 8 unique DNA sequences (named A to H ). The sequences had highest similarity to the human KRTAP20-1 sequence, and this suggests that they are variants of ovine KRTAP20-1 . Among these variants, a 12-bp insertion/deletion and 6 single nucleotide poly- morphisms (SNPs), including one 5′ untranslated region (UTR ) SNP, one 3′ UTR SNP, and 2 nonsynonymous SNPs, were detected. Variant A was found to be associated with a decrease in mean fiber diameter, fiber diameter standard deviation, and prickle factor, whereas variant C was associated with increased greasy fleece weight and decreased wool yield. These associations persisted after adjusting for the effect of 2 nearby KRTAPs ( KRTAP6-3 and KRTAP22-1 ) that have also been reported to associate with these wool traits. This suggests that variation in KRTAP20-1 affects wool yield and mean fiber diameter–associated traits, and that this effect is unlikely to be the result of the clustering of these KRTAPs on chromosome 1.